Easier said than done: ABO compatibility and D matching in apheresis platelet transfusions. Issue 8 (11th March 2015) - Dunbar, Nancy M.; Katus, Matthew C.; Freeman, Christine M.; Szczepiorkowski, Zbigniew M.
<x xml:space="preserve">Abstract</x> BACKGROUND Many hospital transfusion services prioritize ABO plasma compatibility in platelet (PLT) transfusion to minimize risk for acute hemolytic transfusion reactions. In spite of the low risk of D alloimmunization associated with apheresis PLT transfusion, attempts may also be made to provide D– PLTs to D– patients. This study was undertaken to assess how often ABO compatibility and/or D matching occurs at our institution and how the ABO and D mix of our PLT supply impacts PLT selection. STUDY DESIGN AND METHODS We retrospectively reviewed the ABO and D type of all PLTs transfused plus the age, sex, and ABO and D type of all PLT recipients between January 2010 and March 2014 (51 months). RESULTS We provided ABO‐identical PLTs for 5281 (54.6%), ABO plasma–compatible and cellular‐incompatible for 3136 (32.4%), ABO low‐titer plasma‐incompatible and cellular‐compatible for 1150 (11.9%), ABO plasma–incompatible and cellular‐compatible for 30 (0.3%), and ABO plasma–incompatible and cellular‐incompatible for 72 (0.7%). PLT supply did not match PLT demand based on patient ABO type, primarily due to a lower than expected supply of group O PLTs and higher than expected supply of group A and AB. D– patients were less likely to receive ABO‐identical PLT transfusions (p = 0.0008), but were more likely to receive D– PLT transfusions (p < 0.0001). CONCLUSION At our hospital, available inventory and PLT selection practices resulted in the majority of group O patients receiving cellular‐incompatible PLT transfusions. Efforts to provide D– PLTs to D– patients also resulted in fewer D– patients receiving ABO‐identical PLT transfusions.